Proceso de atención de enfermería en el recién nacido con onfalitis - Tello Escobar, Jennifer Gabriela (2018)
We call omphalitis to umbilical cord infection in the newborn, since fortunately hygiene and aseptic measures in cord care are very widespread due to the permeability of the umbilical vessels that persists until approximately 28 days of life but when it appears It can have serious consequences, given the vulnerability of the newborn against infections. As a graduate of the Nursing career, my main objective of my research case study is to apply the process of nursing care in the care of a newborn with neonatal omphalitis, by analyzing a clinical case and thus identify the altered needs, correct and rehabilitate the patient through the application of knowledge, procedures, interventions and nursing care. The fulfillment of the objectives was obtained and for this the assessment was made to the newborn, which allows us to recognize his health status using his clinical file, observation and exploration. The nursing diagnoses were elaborated by identifying the altered patterns. A plan of care was planned according to the most significant needs of the newborn using the NANDA, NIC and NOC taxonomies, then the care plan was carried out, through interventions adjusted and categorized by priority. The evaluation was made to the newborn in order to verify if the nursing interventions carried out helped to improve their health.